Digitalising the Age-Friendly City: Insights from Participatory Action Research - Reuter, Arlind (Int J Environ Res Public Health, 2020)
The World Health Organization’s age-friendly city initiative emerged as a response to the intersecting global trends of population ageing and urbanisation. However, a third global trend—digitalisation—has largely been overlooked in research and policy making relating to age-friendly cities and communities. Within the context of a general shift towards online civic participatory activities, this article explores older adults’ digital citizenship in an age-friendly city in the North of England. Drawing on interviews, observations and field notes from design workshops as part of an ongoing participatory action research project, we consider two key questions. First, how does an age-friendly city stakeholder organisation of older adults make use of digital technologies in order to provide digital information and communications? Second, what is the potential of digital audio to increase civic participation in later life and local engagement with age-friendly issues? Our analysis focuses on two domains of the World Health Organization’s age-friendly city framework: Communication and information and civic participation. First, we report on the stakeholder organisation’s efforts to re-design their digital newsletter in order to provide information and communications to older residents about local work on ageing projects. We then outline the organisation’s efforts, in a public setting, to engage with digital audio as a way to increase the participation of older residents with age-friendly topics. We conclude by suggesting the need to re-frame the role of digital technologies within the age-friendly city, broadening the scope from accessibility towards enhancing digital citizenship opportunities.